The selectivity of the sensory–perception processes - Bagdonas , A. (Psichologija, 1981)
The subject of this article is the selectivity of the sensory-perception processes. Selectivity and attention are considered universal features of the organization of the brain function. The new definition of attention and classification of its kinds are proposed. The relations between attention functional asymmetry, psychological refractoriness are analysed. The emphasis is laid on the importance of the compensation of visual impairement. The second part of the article is devoted to the explanation of the mechanisms of the selective attention. Classical and contemporary theories of attention are discussed and the analysis of neurophysiological and neuropsychological data on selective organization of the brain functions is given. The relationship between attention and habitude is analysed on the basis of E. Sokolov’s theory of neural model of the stimulus. The article is supplied with the data obtained from psychophysiological literature as well as from original studies.